Pembelajaran Audio Visual Dalam Mengembangkan Bahasa Anak Dalam Membaca Al-Qur’an Di Tk Rahmat Damai Aceh - Fatmawati Fatmawati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The researcher aims to see the language development of children through visual audio with group B children with a sample taken 37 children consisting of one class B1 totaling 19 people who made 10 children as the control class and 18 more as the experimental class. Population and Research SamplesPopulation is all data that researchers pay attention to in a scope, and a predetermined time. In this study the subject is determined as a source of data relevant to the problem under study to study and draw conclusions. The sample is the population or subject chosen and determined as a source of data or sources of information from the study. Sampling is done by purposive sampling technique which means it is a technique of determining the sample with certain considerations. Based on the results of research students in classes B1 and B2 show that 3 students get high test results, then 22 students get test results with enough categories, and 12 students get the test results in the low category, in knowing and how in the paragraph. A student is called complete learning if he / she scores at least 75 of the ideal grade. In a class students are called complete learning if the class there are at least 85% of students who complete. Keywords : Audio visual, develops children's language